KAJIAN KARAKTERISTIK OLEORESIN JAHE BERDASARKAN UKURAN DAN LAMA PERENDAMAN SERBUK JAHE DALAM ETANOL - Kawiji, Kawiji; Anam, Choiroel; Manuhara, Godras Jati; Fakhrudin, Muh Ifan (Caraka Tani: Journal of Sustainable Agriculture, 2009)
Ginger (Zingiber officinale rosc.) is one of high-production commodities in Indonesia, particulary in Central Java Province. Nevertheless, in general ginger is usually traded in fresh ginger form or simple processing result, such as dry ginger or ginger powder. Ginger oleoresin is combination of resin and atsiri (volatile) oil derives from ginger powder extraction by using organic solvent. Oleoresin is used as food and beverage flavouring substance having taste and aroma characteristic similar to the original spices. In addition to give ginger hot taste, oleoresin is also hygienic as well as contains natural antioxidant. The research aims to find out whether or not the ginger powder size and submerging duration in ethanol as well as the interaction of them affect the oleoresin characterization produced. The experimental design employed was factorial design with two factors: ginger powder size variations (20 mesh, 30 mesh, 50 mesh) and ginger powder submerging duration variations in ethanol (extraction) (24 hours, 48 hours, 72 hours). The data was obtained from the submerging analysis, density, and solvalibility in alcohol, acid and ester values, as well as phenol content affects the oleoresin characterization produced; the smaller the ginger powder size and the longer the submerging duration of ginger powder in ethanol, the higher are the values of submerging, density, acid value, ester as well as phenol content. The interaction of them only affects the oleoresin density. The range of submerging value obtained is 8-14.5%; density 1.2252-1.2809; solvability in alcohol 1:6-1:10; acid value 0.560-2.248; ester value 5.416-14. 978 as well as phenol content 3-7%.